T7 Exonuclease (GENE 6) is Necessary for Molecular Recombination of Bacteriophage T7 - Lee, Marion (1974)
The role of T7-induced exonuclease (gene 6) in molecular recombination was studied by examining the fate of parental DNA during parental-to-progeny recombination. The method used was to compare infections with T7(+), T7am-6-233 (am gene 6), or T7ts6-136 (ts gene 6) under permissive and nonpermissive conditions. CsCl density gradient analysis of replicative DNA indicated that T7 exonuclease is necessary for recombination to occur, i.e., in the absence of the exonuclease the parental DNA replicated continuously as a hybrid molecule and did not recombine. Further studies under conditions where replicative DNA was denatured and analyzed by CsCl density gradient centrifugation indicated that the exonuclease is also needed for a limited amount of covalent repair of recombinants. A repair function for the T7-induced exonuclease is also suggested by results obtained from alkaline sucrose gradient analysis of replicative DNA. Under conditions nonpermissive for the exonuclease, discontinuities in the DNA accumulated during infection by T7am6-233 or by T7ts6-136.